Genomic variations in plasma cell free DNA differentiate early stage lung cancers from normal controls. Issue 1 (October 2015) - Xia, Shu; Huang, Chiang-Ching; Le, Min; Dittmar, Rachel; Du, Meijun; Yuan, Tiezheng; Guo, Yongchen; Wang, Yuan; Wang, Xuexia; Tsai, Susan; Suster, Saul; Mackinnon, Alexander C.; et al.
Highlights Developed a novel plasma genomic abnormality (PGA) score for CNV analysis. Demonstrated potential use of PGA scores in early detection of lung cancer. Showed detectable gene mutations in early stage lung cancer.